Mandatory Continuing Education: Considerations of Dewey and Ohliger’s Work - Craig M McGill; Tonette S Rocco (Adult Education Research Conference, 2018)
This paper explores discrepancies between Mandatory Continuing Education and Dewey’s ideas on authentic learning. Dewey believed education must serve the goals of the person and the society in which s/he lives.
Keywords: Mandatory continuing education; Ohliger; Dewey